a. Triangle 1: 2x + 7 + x = 3x + 7
Triangle 2: 4x + 4 + 2x = 6x + 4
b. (6x + 4) - (3x + 7) = 3x - 3
c. Triangle 1: 2(3) + 7 + 3 = 13
Triangle 2: 4(3) + 4 + 2(3) = 22
Note: For questions 22–23, your teacher will grade your response to ensure you receive proper credit for your
answer.
22. Look at the given triangles.
a. Write an expression in simplest form for the perimeter of each triangle.
b. Write another expression in simplest form that shows the difference between the perimeter
of the larger triangle and the perimeter of the smaller triangle.
c. Find the perimeter for each triangle when x = 3
3 answers
16x+5-4x+5
The given expression is 16x + 5 - 4x + 5.
Combining like terms, we can add the constants 5 and 5 to get:
= 16x + 10 - 4x
Now, we can combine the x-terms by subtracting 4x from 16x to get:
= 12x + 10
Therefore, the simplified expression is 12x + 10.
Combining like terms, we can add the constants 5 and 5 to get:
= 16x + 10 - 4x
Now, we can combine the x-terms by subtracting 4x from 16x to get:
= 12x + 10
Therefore, the simplified expression is 12x + 10.